1990
DOI: 10.1073/pnas.87.2.628
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of a chromosomal translocation, t(9;14)(p13;q32), in a diffuse large-cell lymphoma cell line expressing the Ki-1 antigen.

Abstract: We have studied a translocation, t(9;14) (pl3;q32), in a diffuse large-cell lymphoma cell line, KIS-1, that expresses the Ki-1 (CD30) antigen. Molecular cloning of the immunoglobulin heavy-chain locus (IGH) of this cell line revealed an unknown segment linked 5' to IGH. The breakpoint on chromosome 14 was 265 base pairs downstream from the 3' border of the JH6 joining gene segment. Class switch recombination deleted most of the constant genes of IGH (CH) and juxtaposed the Ca2 gene downstream of the translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 27 publications
0
35
0
1
Order By: Relevance
“…29 Here we have described the characterization of an IgH P5ki knock-in mouse that reproduces the specific structural and regulatory features of the t(9;14)(p13;q32) translocation identified in the human KIS-1 lymphoma. 9,10,24 One important difference between this knock-in mouse and the corresponding human lymphoma is the fact that the PAX5 insertion in the IgH P5ki allele corresponds to a germline mutation, whereas the IgH-PAX5 translocation in human lymphomas arises in germinal center B cells during late B-cell development. [9][10][11] Consequently, the inserted PAX5 gene is transcribed in all IgH-expressing cells of the knock-in mouse, which contrasts with the exclusive expression of the endogenous Pax5 gene in the B-lymphoid lineage of wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Here we have described the characterization of an IgH P5ki knock-in mouse that reproduces the specific structural and regulatory features of the t(9;14)(p13;q32) translocation identified in the human KIS-1 lymphoma. 9,10,24 One important difference between this knock-in mouse and the corresponding human lymphoma is the fact that the PAX5 insertion in the IgH P5ki allele corresponds to a germline mutation, whereas the IgH-PAX5 translocation in human lymphomas arises in germinal center B cells during late B-cell development. [9][10][11] Consequently, the inserted PAX5 gene is transcribed in all IgH-expressing cells of the knock-in mouse, which contrasts with the exclusive expression of the endogenous Pax5 gene in the B-lymphoid lineage of wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,24 To this end, we generated a human PAX5 minigene containing 1807 bp of its 5Ј flanking sequences and linked this gene via an internal ribosome entry sequence (IRES) to the green fluorescent protein (GFP) gene ( Figure 1A). The PAX5-IRES-GFP expression cassette was inserted into the mouse IgH locus adjacent to the intronic E enhancer in such a way that the D H Q52 element and all 4 J H segments were deleted, thus resulting in a nonfunctional IgH allele ( Figure 1A).…”
Section: Reconstruction Of the Kis-1 Translocation By Insertion Of Pamentioning
confidence: 99%
“…4,5 The presence of a t(9;14) was confirmed by conventional karyotype and FISH analysis, including whole chromosome paint probes for chromosomes 9 and 14 (Vysis, Downers Grove, IL) and the core binding factor ␤ (CBFB) break-apart probe specific for band 16q22 (Vysis). The karyotype was further supported by use of the Chromoprobe Multiprobe System, Octachrome whole chromosome paint assay (Cytocell Ltd., Adderbury, Banbury, UK).…”
Section: Patient Samples and Controlsmentioning
confidence: 99%
“…Initially described in a CD30-positive diffuse large B-cell lymphoma cell line, KIS-1, 4 this translocation involves the paired homeobox-5 (PAX5) gene at 9p13 and the immunoglobulin heavy chain (IgH) gene at 14q32. 5 After its initial characterization, further studies found the t(9;14)(p13;q32) associated with LPL. 6,7 Encoding B-cell-specific activator protein, a B-cell transcription factor, the PAX5 gene has been thought to contribute to the development of lymphoma when brought into close proximity of the IgH.…”
mentioning
confidence: 99%
See 1 more Smart Citation